Hotel website dimension: analyzing customers’ preferences / Azdel Abdul Aziz …[et al.] - Abdul Aziz, Azdel; Mohd Radzi, Salleh; Mohd Zahari, Mohd Salehuddin; Ahmad, Noor Azmi (Universiti Teknologi MARA (UiTM), Malaysia, 2011)
The revolutionary of technology in this modern era is explicitly giving significant impacts to hotel industry and hotel website is use as part of for marketing and business purposes. Various attributes and dimensions have developed through the hotel website. This study is empirically investigates the most important hotel website dimensions to be considered in relation to the international tourists’ preferences. The hotel website dimensions are measured through two categories of variables which are website interactivity and website information. Sample of 400 foreign tourists at Kuala Lumpur International Airport were selected. The most important dimension that attracts online purchasing was selected throughout the study. The study also concluded that website information was the most important variables in hotel website dimension. Practically, this research has shown the importance of understanding in choosing the best and appropriate website dimension to encourage customer to purchase via online.